Heat treatment beats chemicals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In view of the gradual global banning of chemicals used in pest control in packaging fruit, the Cook Islands have trialled and adopted a viable alternative in heat treatment which meets quarantine requirements for their exports of papaya. In a good...